Life satisfaction, psychological stress, and present-moment attention: a generalizability study - Jentsch, Armin; Hoferichter, Frances (Frontiers in Psychology, 2024)
During the last decade, many teachers have retired early, leading to increased discussions about how to improve and maintain their mental health. To address this concern early, we designed an online seminar covering the field of positive psychology by emphasising on mindfulness, positive emotions about one’s future, and resources for pre-service teachers. The seminar was designed to increase their wellbeing, as well as to decrease psychological stress. To explore the sensitivity of our measures to change, we investigate the following research questions: To what extent do we assess trait or state variability in students’ outcomes and what are the levels of reliability achieved? Fifty-four students in their second year at a German university (median age 22 years) participated and they were asked to fill in questionnaires assessing their life satisfaction, psychological stress, and present-moment attention during each of nine sessions over the course of a semester. We performed Generalizability and Decision Studies to estimate variability between-students and within-students, error of measurement, as well as reliability. Our results show that life satisfaction and psychological stress reached high reliability, suggesting that students’ trait and state variability were both assessed with high accuracy. On the other hand, the assessment of present-moment attention would benefit from adding more items to the questionnaires or collecting data from more sessions. We discuss how our findings impact research and practice.